Effects of polymeric training on explosive power in young male basketball - Morsal, B.; Shahnavazi, A.; Ahmadi, A.; Zamani, N.; Tayebisani, M.; Rohani, A. (European Journal of Experimental Biology, 2014)
The main objective of this study sees other explosive polymeric exercises basketball Semnan were young men. In this study 30 individuals athletes basketball two experimental (n =15, Age: 24/10 = 3/23 years, height: 176/22 = 4/91 m, Weight: 71/27 =4/20 kg) and control (n =15, age: 23/27 = 5/01 years, height: 180/13 =4/20 m, weight: 76/07 = 5/28 kg) groups. Voluntarily participated in this study: The experimental group received a 6-week; 3-week training session conducted their own The statistical t-test at a significance level of %5 alpha was used to derive the results. The results showed that polymeric training on explosive strength variables has a significant impact. Seems that polymeric training may have an influence on anaerobic power.